2022
DOI: 10.1177/17562848221078441
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients with recurrent Clostridioides difficile infections

Abstract: Background: The health-related quality of life (HrQoL) can be substantially affected in patients with recurrent Clostridioides difficile infection (rCDI) but the impact of effective treatment of the infection remains unclear. This study aimed to evaluate the HrQoL in patients with rCDI and estimate the gain in HrQoL associated with effective treatment of rCDI. Methods: Patients’ HrQoL was estimated based on EuroQol 5-Dimensions 3-Levels (EQ-5D-3L) questionnaires obtained from a Danish randomised controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…La ausencia de eventos adversos en nuestro paciente post-TMF muestra que esta es una estrategia válida en pacientes mayores de 65 años, tal como ha sido señalado en otra publicación nacional 13 . Recientemente, un estudio aleatorizado contralado mostró que el TMF mejora la calidad de vida de los pacientes con ICD recurrente 15 , situación que sucedió en nuestro paciente. Además, el TMF Trasplante de microbiota fecal en ifección recurrente por Clostridiodes difficile -P. Núñez et al sería una estrategia costo-efectiva al compararla con el tratamiento antimicrobiano, al prevenir de manera más eficaz los episodios de recurrencia 16 .…”
Section: Discussionunclassified
“…La ausencia de eventos adversos en nuestro paciente post-TMF muestra que esta es una estrategia válida en pacientes mayores de 65 años, tal como ha sido señalado en otra publicación nacional 13 . Recientemente, un estudio aleatorizado contralado mostró que el TMF mejora la calidad de vida de los pacientes con ICD recurrente 15 , situación que sucedió en nuestro paciente. Además, el TMF Trasplante de microbiota fecal en ifección recurrente por Clostridiodes difficile -P. Núñez et al sería una estrategia costo-efectiva al compararla con el tratamiento antimicrobiano, al prevenir de manera más eficaz los episodios de recurrencia 16 .…”
Section: Discussionunclassified
“…Recently, fecal microbiota transplantation (FMT) has proved to be an effective therapy for recurrent and resistant CDI. It appears to be safe in short‐ and long‐term follow‐up, and provides a positive impact on the health‐related quality of life 1,2,6–10 . Several studies have suggested that FMT is a promising treatment for severe and fulminant CDI 11–16 .…”
Section: Introductionmentioning
confidence: 99%
“…It appears to be safe in short-and long-term follow-up, and provides a positive impact on the health-related quality of life. 1,2,[6][7][8][9][10] Several studies have suggested that FMT is a promising treatment for severe and fulminant CDI. [11][12][13][14][15][16] However, the impact of FMT on reducing the mortality of patients with severe and fulminant CDI has not been rigorously studied.…”
mentioning
confidence: 99%
“…In the USA, rCDI is a significant public health challenge, accounting for ~75 000–175 000 cases annually 5 , 7 . In addition to the economic burden on patients, an active episode of rCDI significantly impairs the quality of life of these patients 9 . All these mandates for effective prevention strategies to decrease the incidence of rCDI.…”
mentioning
confidence: 99%